2022
DOI: 10.1029/2022gl098599
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Steady State in Coastal Aquifers Is Driven by Multi‐Scale Cyclical Processes, Controlled by Aquifer Storativity

Abstract: Coastal aquifers supply freshwater to nearly half the global population, yet they are threatened by salinization. Salinities are typically estimated assuming steady‐state, neglecting the effect of cyclical forcings on average salinity distributions. Here, numerical modeling is used to test this assumption. Multi‐scale fluctuations in sea level (SL) are simulated, from tides to glacial cycles. Results show that high‐frequency fluctuations alter average salinities compared with the steady‐state distribution prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…However, the pronounced loss of the freshwater lens along the MS transects on South Beach (and potentially concomitant vertical lens thinning) suggest that erosion has been the major SWI driver along the MS transect. In agreement with past studies, we demonstrate that short‐term groundwater monitoring programs only present a snapshot of coastal groundwater dynamics and are not representative of long‐term continuous changes in subsurface salinity distributions (Grünenbaum et al., 2023; Heiss & Michael, 2014; Paldor, Frederiks, & Michael, 2022). Coastal aquifers are challenging to monitor directly, and long‐term monitoring is prohibitively expensive, forcing coastal water resource management to rely heavily on numerical models calibrated to few field observations (Werner et al., 2017).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, the pronounced loss of the freshwater lens along the MS transects on South Beach (and potentially concomitant vertical lens thinning) suggest that erosion has been the major SWI driver along the MS transect. In agreement with past studies, we demonstrate that short‐term groundwater monitoring programs only present a snapshot of coastal groundwater dynamics and are not representative of long‐term continuous changes in subsurface salinity distributions (Grünenbaum et al., 2023; Heiss & Michael, 2014; Paldor, Frederiks, & Michael, 2022). Coastal aquifers are challenging to monitor directly, and long‐term monitoring is prohibitively expensive, forcing coastal water resource management to rely heavily on numerical models calibrated to few field observations (Werner et al., 2017).…”
Section: Resultssupporting
confidence: 90%
“…Further, models that inappropriately assume a present‐day snapshot of coastal groundwater dynamics is representative of steady‐state initial conditions prior to future climatic forcing will produce invalid results. This emphasizes the importance of including the continuous response of coastal aquifers to multi‐scale forcing in alignment with the suggestions of Paldor, Frederiks, and Michael (2022). Our results highlight the importance of erosion and suggest that desktop reviews to assess past SWI should begin with assessing past erosion via analysis of aerial imagery or publicly available LiDAR data.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The 10‐year mark was chosen because past studies have reported that aquifers reached potable conditions within about 10 years of a storm event (Anderson & Lauer, 2008; Yang et al., 2013). Importantly, recovery times that are longer than surge recurrence times may result in an accumulated salinization effect (Paldor et al., 2022). However, for the studied site and for small islands in general, it is likely that full recovery is reached on shorter time scales and therefore we neglected the effect of recurring storms.…”
Section: Methodsmentioning
confidence: 99%